PENERAPAN SANKSI PIDANA KETENAGAKERJAAN TERHADAP PELAKU USAHA YANG TIDAK MEMBAYAR UPAH KARYAWAN SESUAI HUKUM KETENAGAKERJAAN - Permana, Yana Sukma (LPPM STIH Awang Long, 2024)
Wages are the rights of workers or employees that are received and expressed in the form of money as compensation from entrepreneurs or employers to workers which are determined and paid according to work agreements or statutory regulations. There are criminal sanctions against companies that pay minimum wages. and minimum enforcement of criminal sanctions against companies that pay workers' wages below the minimum wage, enforcement of criminal labor sanctions against business actors who do not pay their workers' wages in accordance with labor law. Wages are a fundamental element in the employment relationship between workers and employers. In the context of labor law in Indonesia, employers are obliged to pay workers' wages in accordance with the provisions set by the government. This obligation is regulated in Law Number 13 of 2003 concerning Employment and strengthened through Law Number 11 of 2020 concerning Job Creation. Enforcement of criminal law sanctions in employment cases related to employee wages faces various complex obstacles. Even though there are strict legal instruments, as regulated in Law no. 11 of 2020 concerning Job Creation, the application of criminal sanctions for companies that violate minimum wage provisions is still rare. These obstacles are not only caused by legal factors themselves, but also by other factors such as weak law enforcement, limited facilities and infrastructure, as well as the influence of culture and community structure. Overall, law enforcement is an effort to realize the values ​​of justice and legal certainty.